The HEM Lines: A New Library of Homozygous Arabidopsis thaliana EMS Mutants and its Potential to Detect Meiotic Phenotypes - Capilla-Perez, Laia; Solier, Victor; Portemer, Virginie; Chambon, Aurelie; Hurel, Aurelie; Guillebaux, Alexia; Vezon, Daniel; Cromer, Laurence; Grelon, Mathilde; Mercier, Raphael (Frontiers in Plant Science, 2018)
Genetic screens have been crucial for deciphering many important biological processes, including meiosis. In Arabidopsis thaliana, previous forward screens have likely identified almost all the meiotic genes that when mutated lead to a pronounced decrease in fertility. However, the increasing number of genes identified in reverse genetics studies that play crucial roles in meiosis, but do not exhibit strong phenotypes when mutated, suggests that there are still many genes with meiotic function waiting to be discovered. In this study, we produced 897 Arabidopsis thaliana homozygous mutant lines using Ethyl Methyl Sulfonate (EMS) mutagenesis followed by either single seed descent or haploid doubling. Whole genome sequencing of a subset of lines showed an average of 687 homozygous mutations per line, 193 of which (28%) modify a protein sequence. To test the power of this library, we carried out a forward screen looking for meiotic defects by observing chromosomes at metaphase I of male meiosis. Among the 649 lines analyzed, we identified 41 lines with meiotic defects. Of these, 18 lines had an obvious candidate causal mutation, namely a STOP or splicing site mutation in a gene previously shown to play a role in meiosis (ATM, MLH3, MLH1, MER3, HEI10, FLIP, ASY4, FLIP, PRD2, REC8, FANCL and PSS1). Interestingly, this was the first time that six of these genes were identified in a forward screen in Arabidopsis (MLH3, MLH1, SGO1, PSS1, FANCL and ASY4). These results illustrate the potential of this mutant population for screening for any qualitative or quantitative phenotype. Thus, this new mutant library is a powerful tool for functional genomics in Arabidopsis thaliana. The HEM (Homozygote EMS Mutants) lines are available at the Versailles Arabidopsis stock center.